Progress in Renewable Energies Offshore : Proceedings of RENEW 2016, 2nd International Conference on Renewable Energies Offshore, Lisbon, Portugal, 24-26 October 2016 /: Proceedings of RENEW 2016, 2nd International Conference on Renewable Energies Offshore, Lisbon, Portugal, 24-26 October 2016. ([2016]) - Unknown
No abstract available